Chronic Budd-Chiari syndrome due to obstruction of the intrahepatic portion of the inferior vena cava. Issue 5 (May 1972) - Datta, D. V.; Saha, S.; Singh, Samanta A. K.; Gupta, B. B.; Aikat, B. K.; Chugh, K. S.; Chhuttani, P. N.
Abstract : Clinical features of obstruction of the intrahepatic portion of the inferior vena cava were observed in five out of the 11 patients with the Budd-Chiari syndrome seen during the last four years. These patients apparently formed a distinct group from the remaining six and resembled in clinical course, biochemical features, haemodynamic findings, and radiological investigations the patients described as cases of membranous obliteration of the intrahepatic portion of the inferior vena cava. The present study reports five such patients diagnosed with the help of venous catheterization, percutaneous hepatography, and haemodynamic studies. The value of distinguishing these patients from those with obstruction due to hepatic vein occlusion is highlighted because of the difference in the prognosis and treatment.